2017
DOI: 10.4172/2155-6148.1000751
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Bilateral Ilioinguinal and Iliohypogastric Nerve Block for Post Caesarean Delivery Under Spinal Anaesthesia, 2016. Double blind randomized Study

Abstract: Background: Pain after cesarean section is a common phenomenon. Optimal postoperative pain control is paramount as it facilitates early mobilization of the mother, decrease patient morbidity, improve mother -new born bonding and patient satisfaction. This study was designed to determine the analgesic efficacy of bilateral ilioinguinal and iliohypogastric nerve block for caesareans delivery under spinal anaesthesia in the first 24 post-operative hours, Gondar University hospital, Northwest Ethiopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…In agreement with our results, Nigatu et al reported a significant decrease in pain numerical rating scale during rest or movement in the nerve block group (P < 0.05). The nerve block group had significantly lower pain scores than controls at all measurement times (23). Consistent with our results, Sakalli et al reported that the iliohypogastric ilioinguinal nerve block was significantly associated with lower VAS scores than the sham block.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our results, Nigatu et al reported a significant decrease in pain numerical rating scale during rest or movement in the nerve block group (P < 0.05). The nerve block group had significantly lower pain scores than controls at all measurement times (23). Consistent with our results, Sakalli et al reported that the iliohypogastric ilioinguinal nerve block was significantly associated with lower VAS scores than the sham block.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the number of patients requiring rescue analgesia was lower in the block group than in the control group (59.4 vs. 100%, respectively, P < 0.001). In line with our findings, another study reported a significantly longer time to the first analgesic request in the nerve block group than in controls (12 in cases vs. 4 hours; P < 0.001) (23). Yucel et al also reported that the first analgesic request time was significantly longer in the nerve block group than in controls (26).…”
Section: Discussionsupporting
confidence: 91%
“…We included 114 trials (8730 women) in our final network analysis, 73 (64%) of which reported the primary outcome of morphine equivalent dose in the first 24 postoperative hours for 5126 (59%) women (Fig. 1 and online Supporting Information, Table S1) [14–127]. Placebo vs. transversus abdominis plane injection in 11 trials was the most common direct comparison.…”
Section: Resultsmentioning
confidence: 99%
“…1). 7,9,[22][23][24][25][26][27][28][29][30][31][32] Of these, 433 patients were enrolled in the II-IH block group and 425 were assigned to the control group. The characteristics of the included studies are shown in Table 1.…”
Section: Comprehensive Literature Searchmentioning
confidence: 99%